2019
DOI: 10.1017/s1368980019000569
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopia’s high childhood undernutrition explained: analysis of the prevalence and key correlates based on recent nationally representative data

Abstract: ObjectiveTo examine the contribution of child, maternal and household factors in stunting, wasting and underweight among children under 5 years in Ethiopia.DesignQuantitative cross-sectional design based on nationally representative data.SettingUrban and rural areas of Ethiopia.ParticipantsYounger (0–24 months; n 4199) and older age groups (25–59 months; n 5497), giving a total of 9696 children.ResultsAmong the younger age group, 29 % were stunted, 14 % were wasted and 19 % were underweight; and among the olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 58 publications
4
18
1
Order By: Relevance
“…We did not find any significant association between sanitation, water source and hygiene variables with HAZ in children under five years of age, which contradicts observations in other studies [ 46 , 47 ]. The lack of a true control group, having participating households with similar characteristics (all from resource-poor settings), and a relatively small sample size of the current study make it more difficult to assess such associations, compared to those involving socio-economically diverse study populations and larger sample sizes [ 48 , 49 ]. Use of a small sample size from a localised area has been mentioned as a potential reason for non-significant results from improved toilet and water sources, compared to other studies that used larger sample size and more than one population from different settings [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any significant association between sanitation, water source and hygiene variables with HAZ in children under five years of age, which contradicts observations in other studies [ 46 , 47 ]. The lack of a true control group, having participating households with similar characteristics (all from resource-poor settings), and a relatively small sample size of the current study make it more difficult to assess such associations, compared to those involving socio-economically diverse study populations and larger sample sizes [ 48 , 49 ]. Use of a small sample size from a localised area has been mentioned as a potential reason for non-significant results from improved toilet and water sources, compared to other studies that used larger sample size and more than one population from different settings [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Climate change, namely rainfall, drought, and temperature change, does predict some of the variation in child stunting in Ethiopia ( 18 , 76 ), whereas the limited evidence of the impact of food shocks on stunting outcomes tends to show a lack of association ( 78 , 79 , 80 ). Increased wealth was found to be positively associated with HAZ and thus negatively associated with stunting in a large number of studies ( 16 , 17 , 19–21 , 23–27 , 29 , 31 , 34 , 37 , 38 , 47 , 60 , 66 , 77 , 81 , 82 , 83 , 96 ), whereas some found no association ( 30 , 48 , 64 , 84 , 85 ). Women's empowerment was difficult to quantify, and studies examining this variable suggested that the impact of proxies such as households being headed by women ( 23 , 25 , 30 , 32 , 47 ), women's autonomy ( 85 ), and mothers’ employment ( 26 , 37 , 48 , 86 ) had conflicting or no association with HAZ in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Increased wealth was found to be positively associated with HAZ and thus negatively associated with stunting in a large number of studies ( 16 , 17 , 19–21 , 23–27 , 29 , 31 , 34 , 37 , 38 , 47 , 60 , 66 , 77 , 81 , 82 , 83 , 96 ), whereas some found no association ( 30 , 48 , 64 , 84 , 85 ). Women's empowerment was difficult to quantify, and studies examining this variable suggested that the impact of proxies such as households being headed by women ( 23 , 25 , 30 , 32 , 47 ), women's autonomy ( 85 ), and mothers’ employment ( 26 , 37 , 48 , 86 ) had conflicting or no association with HAZ in Ethiopia. Parental education has been shown to be positively associated with HAZ and negatively associated with stunting in the vast majority of both national ( 16–21 ) and subnational studies ( 22–27 , 29–32 , 96 , 103 ), although some studies found no association ( 22 , 34 , 38 , 47 , 48 , 59 , 64 , 82 , 86 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations